CLIL METHODS IN TEACHING ENGLISH TO PRIMARY CLASS PUPILS - Madaminova Mohlaroyim Rustambek qizi (Galaxy International Interdisciplinary Research Journal, 2021)
This article describes the of learning and teaching English language in the primary classroom in Uzbekistan,discovers successful and effective ways of learning to take place take into account CLIL method of teaching English to young learner.